Severe acute hepatitis of unknown origin in children: Clinical issues of concern - Fu, Hai-Jing; Zhou, Min; Huang, Zhi-Hui; Chen, Yong-Xu; Wu, Xiao-Xin (Journal of translational internal medicine, 2023)
A positive COVID-19 test at any time before the appearance of hepatitis symptoms was not statistically significant, because 11.9% of hepatitis cases were positive for COVID-19 compared with 15.6% in the random sample. [...]blood sample analysis showed no significant difference in the presence of SARS-CoV2 antibodies between hepatitis cases and age-matched patient controls. According to the CDC reports, in June 2022, among 252 (83%) PUIs tested for adenovirus in at least one specimen type (stool, respiratory fluid, serum, plasma, or whole blood), 45% were positive. The hypothesis explored the possibility that when the SARS-COV-2, Human adenoviruses, or other viruses infect children, their weakened immune system cannot eliminate the viruses, and viral persistence in the gastrointestinal tract could result in repeated release of viral proteins across the intestinal epithelium, causing immune activation. Given that many of the confirmed cases have shown a positive result for Human adenovirus or SARS-CoV-2, measures to reduce children’s exposure to viruses are required.